Airfield and Highway Pavements 2023 Innovation and Sustainability in Airfield and Highway Pavements Technology. - Garg, Navneet (American Society of Civil Engineers, 2023)
This collection contains 29 peer-reviewed papers on sustainability and innovation in pavements presented at the International Airfield and Highway Pavements Conference 2023, held in Austin, Texas, June 14-17, 2023.
Keywords: elektronické knihy; electronic books